PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN BLENDED UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Rahima Safitra Pane; Yuni Rhamayanti; Haritsah Hammamah Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The type of research used is Classroom Action Research (CAR) using two learning cycles, with the subject of class X-1 SMA Negeri 1 Batangtoru totaling 25 people. While the object of this research is the use of problem-based learning model with Blended to improve students' mathematical problem solving ability. Before the instrument was used, a test trial was conducted to see the validity and reliability of the test. Of the 6 test questions in the first cycle and 6 test questions in the second cycle, 5 test questions in the first cycle were valid (valid) and 5 test questions in the second cycle were valid (valid), and all test questions were reliable with a test reliability coefficient of 0.926 with a level high reliability and has a validation correlation with the moderate category. The average result of the students' mathematical problem solving ability test on the students' mathematical problem solving ability test in the first cycle was 68.80 in the